Kaffet, blomman och det tända ljuset: Om gåvan, social solidaritet och senmodernitet - Lundälv, Jörgen; Larsson, Per-Olof (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
What is gift-giving? This article presents a brief theoretical overview concerning the concept of gift-giving in the modern society. The concept of gift is an old social and cultural phenomenon. In this article we compare the concept of gift and gift-giving with the concept of recognition. The recognition of the identity is a continuously ongoing process in the society. The aim of the article is to discuss some interesting perspectives of gift-giving in Sweden during recent period.